Penelitian ini bertujuan untuk mengetahui pelaksanaan kegiatan pembuka, inti dan penutup dalam proses belajar mengajar berbasis PBL menggunakan media gc (Google Classroom) pada mapel sosiologi di kelas X IPS 1 SMA Negeri 6 Pontianak. Metode yang digunakan - Syahrul Maulana; Nuraini Asriati; Riama Al Hidayah; Okianna Okianna; Nining Ismiyani (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2024)
This study aims to determine the implementation of the opening, core and closing activities in the PBL-based teaching and learning process using gc media (Google Classroom) in the sociology subject in class X IPS 1 SMA Negeri 6 Pontianak. The method used is descriptive qualitative. Data collection techniques used observation techniques, interviews, and communication tools, data collection tools, namely observation guides, interview guides, and documentation, data analysis techniques, namely data reduction, data presentation, drawing conclusions and verification, testing the validity of the data was the extension of observations and triangulation. The results of the study show that in implementing sociology learning using lesson plans (RPP) using the PBL model in the Google Classroom application which consists of preliminary activities, core activities and closing activities.